Toll-like Receptors and Inflammatory Bowel Disease - Lu, Yue; Li, Xinrui; Liu, Shanshan; Zhang, Yifan; Zhang, Dekai (Frontiers in Immunology, 2018)
Inflammatory bowel disease (IBD) is one relapsing and lifelong disease that affects millions of patients worldwide. Increasing evidence has recently highlighted immune-system dysfunction, especially toll-like receptors (TLRs)-mediated innate immune dysfunction, as central players in the pathogenesis of IBD. TLRs and TLR-activated signaling pathways are involved not only in the pathogenesis but also in the efficacy of treatment of IBD. By understanding these molecular mechanisms, we might develop a strategy for relieving the experience of long-lasting suffering of those patients and improving their quality of life. The purpose of this review article is to summarize the potential mechanisms of TLR signaling pathways in IBD and the novel potential therapeutic strategies against IBD.